2011
DOI: 10.1510/icvts.2011.275602
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic total arch replacement without hypothermic circulatory arrest to treat aortic distal arch aneurysm in a patient with cold agglutinin disease

Abstract: Cold agglutinin disease although rare, can lead to serious complications for patients undergoing cardio-thoracic surgery, especially when cardiopulmonary bypass is applied under hypothermic circulatory arrest. We describe normothermic total arch replacement without hypothermic circulatory arrest in a patient with cold agglutinin disease. The patient tolerated all procedures well and did not develop cerebral ischemia due to surgical maneuvers or thrombotic or haemolytic complications due to cold agglutinin dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…5,6 Fatal complications have been reported, with exacerbations of hemolysis triggered by febrile illness, trauma, or surgery. [38][39][40][41][42][43][44][45] In addition to hemolysis, clinical manifestations include coldinduced circulatory symptoms; livedo reticularis, Raynaud disease, acrocyanosis and, rarely, cutaneous necrosis. 20,[46][47][48][49] Berentsen et al 5 reported cold-induced symptoms in more than 90% of patients.…”
mentioning
confidence: 99%
“…5,6 Fatal complications have been reported, with exacerbations of hemolysis triggered by febrile illness, trauma, or surgery. [38][39][40][41][42][43][44][45] In addition to hemolysis, clinical manifestations include coldinduced circulatory symptoms; livedo reticularis, Raynaud disease, acrocyanosis and, rarely, cutaneous necrosis. 20,[46][47][48][49] Berentsen et al 5 reported cold-induced symptoms in more than 90% of patients.…”
mentioning
confidence: 99%
“…However, it was ruled out for two reasons: 1) the lack of an adequate proximal landing zone for the deployment of the endovascular graft, and 2) the need for surgical resection of the diverticulum in order to resolve the dysphagia. Although some authors have described aortic arch replacement without DHCA [1,2], the traditional surgical approach for the treatment of this pathology requires CPB and DHCA and is associated with mortality and morbidity [3,4]. We ruled out this option in view of our patient's malnourishment and frail condition.…”
Section: Discussionmentioning
confidence: 94%
“…Although some authors have described aortic arch replacement without DHCA [1,2], the traditional surgical approach for the treatment of this pathology requires CPB and DHCA and is associated with mortality and morbidity [3,4]. We ruled out this option in view of our patient's malnourishment and frail condition.…”
Section: Discussionmentioning
confidence: 94%